Sensor PCF-SPR Terpolarisasi Ganda untuk Deteksi Alkohol pada Suhu Rendah - Azhar Azhar; Khaikal Ramadhan; Dedi Irawan (Jurnal Penelitian Pendidikan IPA, 2022)
We have observed a numerical simulation of the PCF-SPR sensor detecting alcohol concentration at low temperatures. The investigation was carried out using the finite element method on the PCF-SPR geometric structure. We use a simple geometry structure of the sensor by using fused silica and gold as the sensor’s core and plasmonic material. Observations were made in the alcohol concentration range of 15%, 40%, 60%, and 70%. In the literature, we find the refractive index of each alcohol concentration and input its value into the proposed sensor. The proposed sensor shows that the sensor has a sensitivity in detecting alcohol concentrations at low temperatures of 91 nm/%. In the end, we obtained the optimal sensor components and the sensor can detect the alcohol concentration at low temperatures